Variability studies for fruit traits and the inheritance pattern of peel and pulp colour in guava - Megha, M; Vasugi, C; Anuradha, S; Kanupriya, C; Hima, B K; Ravishankar, K V; Shivashankara, K S; Sudhakar Rao, D V (Plant Science Today, 2026)
Guava, an important nutritionally rich fruit crop, exhibits a wide range of variations for peel and pulp colour. The present investigation was carried out during 2022-24 at ICAR-Indian Institute of Horticultural Research (IIHR), Bengaluru, in intervarietal progenies of guava derived from Purple Local × Arka Poorna to know the extent of genetic variability present in various fruit traits and the inheritance of peel and pulp colour based on intervarietal progenies that fruited consistently over two seasons. The result revealed high to low Genotypic Coefficient of Variance (GCV) and Phenotypic Coefficient of Variance (PCV) for the measured traits. The highest PCV and GCV were exhibited for fruit weight (FW) (37.44 % and 21.56 %), number of seeds/100 g of fruit (NS) (42.69 % and 25.58 %) and seed weight/100 g of fruit (SW) (26.08 % and 37.53 %). The high heritability value with high genetic advance was recorded for all the peel and pulp colour traits viz. Peel L* (0.83 % and 50.55 %), Peel a* (0.73 % and 100.77 %), Peel hº (0.89 % and 68.36 %) and Pulp L* (0.67 % and 26.79 %), Pulp a* (0.79 % and 84.54 %), Pulp b* (0.63 % and 44.30 %), Pulp C* (0.67 % and 41.32 %) and Pulp hº (0.80 % and 88.29 %). Whereas, the moderate heritability with high genetic advance was recorded for FW (0.33 % and 25.56 %), diameter of calyx cavity (DCC) (0.56 % and 23.19 %), NS (0.36 % and 31.57 %) and SW (0.48 % and 37.34 %). Further, the segregation analysis for peel and pulp colour in intervarietal progenies of guava demonstrated that there is an epistatic interaction between genes and two genes governing the colour characters and the peel colour was inherited with a segregation ratio of 9:7, indicated there is a complimentary gene action whereas, the pulp colour was inherited with 9:3:4 ratio indicated that there is a supplementary gene action. Thus, based on the high heritability with high genetic advance, it can be inferred that fruit peel and pulp colour, along with the fruit weight, could form a selection criterion in the guava improvement program.